SOCIEDADE, CULTURA E TRATAMENTO ADEQUADO: A GÊNESE DO CONFLITO E A APLICAÇÃO DO MÉTODO AUTOCOMPOSITIVO À LUZ DA TEORIA DO RECONHECIMENTO DE AXEL HONNETH - Silva, Betania Teodora Andrade da (2020)
The authors of classical liberal contractualism and German Idealism are credited with elaborating adverse philosophical currents capable of explaining the origin of society from the elements that form human nature and the motivational genesis of the confl